Analisis Prediksi Kebangkrutan Berdasarkan Model Altman Z-Score Pada PT.Goodyear Indonesia Tbk Periode 2015-2020 - Monika Rosmalinda; M. Rizki Yudha; Reza Febrianti (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of this study was to determine the potential for bankruptcy by using the Altman Z-Score at “PT. Goodyear Indonesia Tbk in 2015 - 2020”. The analytical tool used to determine the potential for bankruptcy in this study is the Altman Z-Score model. This study uses the Altman Z-Score method, this is evidenced by the decreasing value of the Z-Score every year so that very large companies have the potential to go bankrupt. From the results of the analysis and discussion, it can be concluded that during the six years of observation (2015 2020) PT. Goodyear Indonesia experienced a decrease in the Z-Score number. In the last two years of the study, the company was in an unhealthy condition or bankrupt so the company's financial condition was very risky with a very large possibility of bankruptcy and great potential for bankruptcy in the future.